2012
DOI: 10.1080/00029157.2011.650333
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Hypnotherapy for Anxiety Disorders

Abstract: Cognitive hypnotherapy, also known as cognitive-behavioral hypnotherapy (CBH), is applied to the treatment of anxiety disorders. Specific techniques are described and illustrated. The research on CBH is discussed. CBH seems to be at least as effective as behavior therapy (BT) and cognitive-behavior therapy (CBT) treatments that employ imagery and relaxation techniques for anxiety disorders. However, more research is needed because of the lack of adequate studies comparing CBH with BT and CBT. Clinical implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…H. Montgomery, DuHamel, & Redd, 2000; Patterson & Jensen, 2003; Tomé-Pires & Miró, 2012), chronic pain (Elkins, Jensen, & Patterson, 2007; Jensen & Patterson, 2006; Jensen, 2009; G. H. Montgomery et al, 2000; Patterson & Jensen, 2003; Tomé-Pires & Miró, 2012), irritable bowel syndrome (Rutten, Reitsma, Vlieger, & Benninga, 2013; Tan, Hammond, & Joseph, 2005), depression (Alladin, 2012), and anxiety (Golden, 2012; Hammond, 2010). Hypnosis has also been shown to enhance the efficacy and benefits of other therapeutic approaches, such as cognitive-behavioral therapy (Kirsch, Montgomery, & Sapirstein, 1995).…”
mentioning
confidence: 99%
“…H. Montgomery, DuHamel, & Redd, 2000; Patterson & Jensen, 2003; Tomé-Pires & Miró, 2012), chronic pain (Elkins, Jensen, & Patterson, 2007; Jensen & Patterson, 2006; Jensen, 2009; G. H. Montgomery et al, 2000; Patterson & Jensen, 2003; Tomé-Pires & Miró, 2012), irritable bowel syndrome (Rutten, Reitsma, Vlieger, & Benninga, 2013; Tan, Hammond, & Joseph, 2005), depression (Alladin, 2012), and anxiety (Golden, 2012; Hammond, 2010). Hypnosis has also been shown to enhance the efficacy and benefits of other therapeutic approaches, such as cognitive-behavioral therapy (Kirsch, Montgomery, & Sapirstein, 1995).…”
mentioning
confidence: 99%
“…Pediatric/adolescent health care providers’ can help adolescents cope and deal with a wide variety of conditions such as chronic headaches/recurrent abdominal pain, anxiety, depression, grief and bereavement, phobias, anger, family stressors, sleep disorders, or enuresis [36,37,38,39,40,41,42,43,44,45,46,47]. …”
Section: Clinical Hypnosis: An Effective Mind–body Modality For Admentioning
confidence: 99%
“…For example, Kirsch, Montgomery, and Sapirstein (1995) reviewed 18 studies and found that clients receiving cognitive-behavioral therapy enhanced by hypnotherapy showed greater improvement than at least 70% of clients receiving nonhypnotic treatment. Although there is a need for further research on the impact of integrating hypnosis into standard treatment for stress and anxiety disorders specifically (Golden, 2012), there is initial evidence that integrating hypnosis into cognitive-behavioral treatment, therapeutic gains are superior to CBT alone. Therefore, it is theorized that third wave cognitive therapies are not only compatible with hypnosis, but treatment gains may even be enhanced by a hypnotic delivery and reinforcement of content.…”
Section: Integrating Hypnosis Into Standard Therapymentioning
confidence: 99%